POLITIK MASKULIITAS DAN BAHASA SEKSIS: BAPAKISME RIDWAN KAMIL DALAM AKUN INSTAGRAM @RIDWANKAMIL - Bintang Purwaramdhona, Ananda; Adji, Muhamad; Prabasmoro, Tisna (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
The New Order's masculinity politics, which perpetuates hegemonic masculinity through the concept of bapakism, is still influential after the reform. The implications can be seen from the dominance of the "father" image often displayed by politicians via social media, one of whom is Ridwan Kamil. This article aims to explain Ridwan Kamil's construction of masculinity in the Instagram account @ridwankamil using mixed methods by combining a corpus-based digital humanities theoretical framework and concepts of the politics of masculinity and bapakisme. The results of the research show that, Ridwan Kamil predominantly displays hegemonic masculinity through caption language on his Instagram by often positioning himself as "father" and society as "children" and subordinating women using sexist language. This article argues that politicians use political masculinity as rhetoric and ideology to strengthen their position of power and gain support from society, which is also still heteronormative.